Analisa Risiko Kesehatan Dan Keselamatan Kerja (K3) Di Laboratorium Bakteriologi Akademi Analis Kesehatan Manggala Yogyakarta - Destu Satya Widyaningsih; Dela Ulya Safira (Departement of Mathematics Education, 2024)
The Bacteriology Laboratory is one of the laboratories used for practical learning on the Manggala Yogyakarta Health Analyst Academy campus. The Bacteriology Laboratory has dangers and risks causing health and safety risks. Bacteriology practical learning uses samples that have the potential for infection. Apart from infections, there is the potential for work accidents throughout October 2022. The aim of the research is to determine K3 risks in the Bacteriology Laboratory of the Manggala Yogyakarta Academy of Health Analysts. This type of research is quantitative descriptive with a cross-sectional design. The target population in this research is students, laboratory assistants, supervisors. The total population is 103. The sampling technique used was stratified random sampling technique. The results of the Occupational Health and Safety (K3) Risk Analysis research at the AAK Manggala Bacteriology Laboratory showed assessment levels of 2, 3 and 4. The risk assessment level in the Bacteriology Laboratory was classified as low risk.